Biosynthesis of silver nanoparticles by Novosphingobium sp. THG-C3 and their antimicrobial potential. (17th February 2017) - Du, Juan; Singh, Hina; Yi, Tae-Hoo
Abstract: The present study described biosynthesis of silver nanoparticles (AgNPs) using a bacterial strain Novosphingobium sp. THG-C3, isolated from soil, and their application in antibacterial activity. The maximum absorbance values of the synthesized AgNPs was measured at 406 nm in ultraviolet-visible spectrophotometry and were mostly spherical in shape with particle size in range of 8–25 nm by field emission transmission electron microscopy analysis. X-ray diffraction pattern corresponding to planes (111), (200), (220), and (311) demonstrated the crystalline nature of the AgNPs. The synthesized AgNPs exhibited antimicrobial activity against various pathogens inculding Staphylococcus aureus, Candida tropicalis, Pseudomonas aeruginosa, Escherichia coli, Vibrio parahaemolyticus, Candida albicans, Salmonella enterica, Bacillus subtilis, and Bacillus cereus . In addition, the AgNPs in combination with commercial antibiotics enhanced antimicrobial activity against P. aeruginosa, S. enterica, E. coli, and V. parahaemolyticus . The AgNPs synthesized by strain Novosphingobium sp. THG-C3 are comparatively simple, green, cost-effective, and may serve as a potential antimicrobial agent.